Agitation and propaganda work and fight against defeatist sentiments in Khanty-Mansiysk National District at initial stage of the Great Patriotic War - E. V. Leshukova (Омский научный вестник: Серия "Общество. История. Современность")
The study describes main aspects of the agitation and propaganda work of the authorities of the Khanty-Mansiysk National District and analyzes its impact on the socio-political conditions of life and behavior of the population at the initial stage of the Great Patriotic War. The source base of the study is the office documents of the Communist Party of the Soviet Union, stored in the Historical Archive of the Omsk region and the State Archive of Socio-Political History of Tyumen region. The author comes to the conclusion that in the difficult conditions of the beginning of the war with Nazi Germany, the party leadership of the district showed determination and firmness in carrying out measures of a political and educational nature. The intensity and coherence of the work of the district’s party bodies in organizing rallies, meetings, lectures, talks, speeches and other forms of agitation and mass events contributed to strengthening the spiritual uplift of Ugra residents, neutralizing negative political sentiments, thereby ensuring the stability of the internal political situation in one of the rear areas of the country.